FTIZZY CONTROLLERS FOR SINGLE POINTCONTROLLER-I (SPC-l) SYSTEMS - Lzzam A Marouf; Omar W. Abdul-Wahab; Luma A. Kamel (Journal of Engineering, 2024)
Advances in computer technology have introduced computers everywhere. One of the fields that the computers have entered is the field of process control and data acquisition systems. On the other hand, fuzzy control is emerging as an alternative to conventional control to control different systems. this paper is concerned with applying fuzzy control to a locally designed and manufactured process controller. This controller is designated by single point controller-1 (SPC-l)' It is basically a flexible and general-purpose, stand-alone, single-point controller. The CPU section of the SPC-1 is the AT89C5l general purpose microcontroller. The fuzzy control algorithms were imple-mented as programs to be executed by this microcontroller. These programs were written in C language and were translated to machine language by Keil8051 C compiler p Vision V5.1.